Gramsci, Poulantzas and the socialist transition - Galastri, Leandro (Pontifícia Universidade Católica de São Paulo, 2013)
This article defends the hypothesis that the strategic moment in the class struggle to constructan alternative hegemony is when a hegemonic apparatus is created outside of the functionalstructures and institutions of the capitalist state. Therefore, it is necessary to considerthe potential for the expansion of the political practices of the working classes beyond thelimits of bourgeois institutions. It is by debating between the Gramscian perspective of theconcepts of hegemony and ideology, on the one hand, and the reading of those same ideas bystructural Marxism, on the other, that we expect to find the appropriate theoretical frameworkfor the approach suggested here.